Does household’s food and nutrient acquisition capacity predict linear growth in children? Analysis of longitudinal data from rural and small towns in Ethiopia - Mekonnen, Daniel Ayalew (Springer, 2024)
Nutritious foods are unaffordable to the majority of households in lower-income countries. Hence, starchy staples tend to be the main source of diets for men, women, and children, implying poor diet quality and deficiency in key nutrients that are crucial for child’s physical growth and cognitive development. Much of existing studies on child linear growth or stunting examined the impact of current dietary consumption on physical growth even though the effect of diets and nutrition would only be observed with time lag. This study examined the associations between sustained consumption of animal sourced foods (ASFs) and adequate nutrient intakes (measured by the mean nutrient adequacy (MPA)) and linear growth differences among children in rural and small towns in Ethiopia. Using nationally representative longitudinal data, results of fixed effects estimations suggested that a standard deviation increase in the household MPA was associated with a 10–11% increase in the height-for-age z-score; and a 10% increase in the household MPA was associated with a 3.2 – 5.6% reduction in stunting rate in children 6–59 months of age. Results also indicated some associations between past ASFs consumption and current linear growth outcomes in younger children. The gap in the household MPA was over 41%, indicating the need for nutrient-dense ASFs in the household diets despite the sustainability concerns around ASFs. Key implication is that policies and interventions aimed at improving linear growth outcomes of children in rural and small towns in Ethiopia should improve household’s access to ASFs and nutrient acquisition capacity.